(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The objective of the research is to measure the impact of social responsibility on the financial performance of the Bank of Baghdad for the period from 2014 to 2016 (3 years) through discussing and analyzing the level of practice of the Bank of Baghdad for social responsibility and the impact on their financial performance during the period. To measure the independent variable (CSR), the researcher used the CSR Disclosure Index and relied on the ROA as an indicator to measure the dependent variable (financial performance).The results of the research showed the main hypothesis of the research, which states that the social responsibility of the banks has no significant impact on the financial performance. In relation to the disclosure of social responsibility and ROA used. The research concluded with a number of conclusions, the most important of which was that the adoption by the Iraqi private banks of social responsibility activities in general was limited based on the results reached, reflecting the lack of a culture of social commitment and the consequences of its work on society and the country in which it operates, and The financial performance of Iraqi private banks in general is weak due to the results reached as they did not rise to the global Industry Norms associated with banking according to the ratios used by the researcher to measure the Financial Performance of selected Banks.